Lysosomal dysfunction and glycosphingolipid dysregulation in rare and common neurodegenerative diseases - Huebecker, M (2019)
Historically, the rare early-onset neurodegenerative lysosomal storage disorders (LSDs) have been studied as discrete metabolic diseases in their own right. However, in recent years links with more common late-onset neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS) and Parkinson’s disease (PD), have emerged. For example, lysosomal dysfunction, impaired autophagy, and protein aggregation are shared features in these diseases. However, altered lipid homeostasis, especially glycosphingolipid (GSL) dysregulation, is a relatively new research field of interest in PD and even more so in ALS. In this thesis, we provide evidence that GSL metabolism is altered during denervation, in an ALS mouse model, and in ALS patients. We further show that pharmacological modulation of GSL levels, especially the ganglioside GM1a, could be a therapeutic approach for ALS. Mutations in the Gaucher disease-linked lysosomal enzyme GBA are major genetic risk factors for developing PD. In this thesis, we observed that a subset of sporadic PD fibroblasts phenocopied characteristics of lysosomal dysfunction associated with GBA mutations. Furthermore, ageing is the major non-genetic risk factor for adult-onset neurodegenerative diseases. We show that levels of GSLs and activities of lysosomal hydrolases, relevant to PD, are altered in the ageing brain of wildtype mice. Importantly, we demonstrate, in human post-mortem substantia nigra and putamen, that levels of GSLs, especially complex gangliosides such as GM1a, and multiple lysosomal hydrolase activities are reduced during ageing and to a greater extent in sporadic PD. However, these changes were not observed in mouse models of PD, questioning their usefulness as models for PD. Finally, we demonstrate that ganglioside levels in cerebrospinal fluid and serum from PD patients are potential biomarkers for PD. Consequently, existing LSD therapies may hold promise as new therapeutic approaches for treating PD.